Cybernetics and the human sciences. (February 2020) - Geroulanos, Stefanos; Weatherby, Leif
Cybernetics saturates the humanities. Norbert Wiener's movement gave vocabulary and hardware to developments all across the early digital era, and still does so today to those who seek to interpret it. Even while the Macy Conferences were still taking place in the early 1950s, talk of feedback and information and pattern had spread to popular culture – and to Europe. The new science created a shared language and culture for surpassing political and intellectual ideas that could be relegated to a pre-computing tradition, and it refracted or channelled currents developing in fields from manufacturing to human physiology. It produced conceptions of the political world, as well as new forms of historical consciousness. It offered frameworks for structuralist thought, but also for policies regarding manufacturing and technology, international relations, and governmental decision-making. But the rising sense of the breadth, importance, and even shock of cybernetics long remained understudied, even as its intellectual assemblages continued to, well, relay. In devices and the so-called 'digital humanities', a refracted legacy of cybernetics is also visible. From mainframes to category-frameworks, cybernetics is everywhere in our material and intellectual worlds, even as the name and its meaning have faded. To the extent that cybernetics permeates the human sciences and our culture at large, it remains opaque – an only partially visible legacy often deemed too complex to form a simple object of historical narrative. This special issue on cybernetics in the human sciences outlines the history and stakes of cybernetics, as well as the possibilities of returning to it today.